Propeller effect in the transient x-ray pulsar SMC X-2 - Alexander A. Lutovinov; Sergey S. Tsygankov; Roman A. Krivonos; Sergey V. Molkov; Juri Poutanen (IOP PUBLISHING LTD, 2022)
We report the results of the monitoring campaign of the transient X-ray pulsar SMC X-2 performed with the Swift/XRT telescope over the period of 2015 September-2016 January during the Type II outburst. During this event, the bolometric luminosity of the source ranged from similar or equal to 10(39) down to several x 10(34) erg s(-1). Moreover, we discovered its dramatic drop by a factor of more than 100 below the limiting value of L-lim similar or equal to 4 x 10(36) erg s(-1), which can be interpreted as a transition to the propeller regime. These measurements make SMC X-2 the sixth pulsating X-ray source where such a transition is observed and allow us to estimate the magnetic field of the neutron star in the system B similar or equal to 3 x 10(12) G, which is in agreement with independent results of the spectral analysis.